Mechanisms regulating transitory suppressive activity of neutrophils in newborns: PMNs-MDSCs in newborns. Issue 5 (21st June 2022) - Perego, Michela; Fu, Shuyu; Cao, Yingjiao; Kossenkov, Andrew; Yao, Meng; Bonner, Erin; Alicea-Torres, Kevin; Liu, Wangkai; Jiang, Zhilong; Chen, Zhihong; Fuchs, Serge Y; Zhou, Jie; et al.
Abstract: Transitory appearance of immune suppressive polymorphonuclear neutrophils (PMNs) defined as myeloid-derived suppressor cells (PMNs-MDSCs) in newborns is important for their protection from inflammation associated with newly established gut microbiota. Here, we report that inhibition of the type I IFN (IFN1) pathway played a major role in regulation of PMNs-MDSCs-suppressive activity during first weeks of life. Expression of the IFN1 receptor IFNAR1 was markedly lower in PMNs-MDSCs. However, in newborn mice, down-regulation of IFNAR1 was not sufficient to render PMNs immune suppressive. That also required the presence of a positive signal from lactoferrin via its receptor low-density lipoprotein receptor-related protein 2. The latter effect was mediated via NF-κB activation, which was tempered by IFN1 in a manner that involved suppressor of cytokine signaling 3. Thus, we discovered a mechanism of tight regulation of immune suppressive PMNs-MDSCs in newborns, which may be used in the development of therapies of neonatal pathologies. Graphical Abstract: A mechanism of temporal control of PMN-MDSC in newborns identified that involves lactoferrin mediated positive and type I interferon mediated negative regulation.